Influence of music on the hearing and mental health of adolescents and countermeasures - Chen, Li (Frontiers in Neuroscience, 2023)
This review elaborates on the influence of music on the psychological well-being of adolescents, covering the potential advantages, drawbacks, and necessary strategic interventions associated with music exposure. Initially, we characterize music and delve into a multifaceted classification system. Music, as a pervasive art form, is categorized based on regional and national parameters, and it also distinguishes through the assorted genres and traits. The mental well-being of adolescents is significantly influenced by music through mechanisms such as the facilitation of emotional expression and regulation, fortification of social bonds and the sense of belonging, as well as the fostering of creativity and cognitive development.Nonetheless, music, if misused or associated with inappropriate content, could elicit a spectrum of issues ranging from auditory impairment, diversion of attention, addiction tendencies, to the induction of negative emotions. To counteract these potential hazards, we propose several mitigation strategies including the selection of appropriate music styles, the establishment of a wholesome music environment, the promotion of the constructive role of music education, and fostering active participation in music activities among the youth. In conclusion, we underscore the necessity of a collaborative endeavor from all sectors of society to ensure a healthy music environment for the youth, which in turn would enhance the positive influence of music on the mental health development of this population.